Asymmetric Information and Corporate Social Responsibility. (March 2016) - Lopatta, Kerstin; Buchholz, Frerich; Kaspereit, Thomas
This article addresses the question whether companies benefit from their commitment to corporate social responsibility (CSR). The authors argue that firms which score high on CSR activities build investor confidence and find evidence that they benefit from lower information asymmetry. The authors measure information asymmetry by insider trading, which is defined as the trading of a company's shares by corporate insiders who have an information advantage with the aim to reap gains or avoid losses. Using a sample of U.S. firms listed in the MSCI World Index during the period 2004 to 2013 and the firm- and industry-level CSR rating from Global Engagement Service (GES), the authors show that insider transactions in firms with a high score on CSR activities lead to lower abnormal returns. This investigation extends current literature on the business case for CSR by explaining the influence of CSR activities on asymmetric information.